Experimental and theoretical study of the features of the amplitude-frequency response features of the anharmonic Duffing oscillator - B. A. Kalashnikov; V. V. Bokhan; V. E. Smolko (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
In this paper, experimental waveforms of the bifurcation phenomena in a Duffing oscillator weakly damped by viscous friction. The bifurcation points are found by solving the numerical solution of a harmonically linearized system with respect to the square of the frequency and the square of the amplitude. Approximate dimensionless expressions for amplitudes and their corresponding frequencies at the bifurcation points are proposed. The comparison of experimental and theoretical amplitudefrequency characteristics and their values at these points is given.